Main Puteri: An analysis of the physical movements of Tok Puteri- Pak Mat Jedok through laban movement analysis / Dayang Mariana Abang Bolhassan - Dayang Mariana , Abang Bolhassan (2019)
Main Puteri or Main Peteri/Teri is a type of Malay traditional healing ritual that involves trance in which the shaman becomes the vehicle or placing for a spirit during healing rituals. It is commonly practiced by the Kelantanese for curing illness related to three causes of illnesses such as (a) angin literally “wind” that possesses special connotation in the context of Main Puteri and other healing traditions of the Malays, (b) possession by disease-causing spirit – hantu, and(c) the weakening or loss of a person’s soul-substance – semangat (Ghulam 2004). Main Puteri healing ceremony is usually performed at night at a specific space called gelanggang or privately held at the home of the sick person. The existence of Main Puteri is said to have been developed and practiced before the arrival of Islam in the area located at the north-eastern part of Peninsula Malaysia – Kelantan, Terengganu, and the area close to the border of southern Thailand. Main Puteri consists of a pair of extremely important functionaries known as Tok Puteri or Bomoh Puteri and Tok Minduk. Tok Puteri, a shaman who is an experience individual responsible for healing the illness of the sick person, enters a state of trance to facilitate spirits descent during the healing session. Tok Minduk, on the other hand, functions as an interrogator who acts as the middlemen on behalf of the patient questioning the entranced Tok Puteri during the healing session and also the principal musician playing rebab (three –stringed spiked fiddle) assisted by musicians who play different types of traditional music instruments. This research however concerns with the individual style of the physical movements of Tok Puteri - Pak Mat Jedok, performing in Main Puteri. Pak Mat Jedok was selected as the subject of this study because he is a very established and well known Tok Puteri in Kelantan. The objectives are to understand the important aspects of how the physical movement reveals Pak Mat’s individual style as Tok Puteri in the performance of Main Puteri and at the same time shed light in understanding the theory, practical and overall dynamic of the physical movements by Pak Mat Jedok. Through this study, Pak Mat’s dominant style is revealed by using Laban Movement Analysis (LMA) consisting of the four major components - Body, Effort, Shape and Space (BESS).The analysis of his physical movement is based on video recorded materials from 2011, 2014 and 2017. Finally, through LMA in finding the quality of the movements, this study showed the use of Awake State, Rhythm State and Stable State are more frequent and extensive than other States that have resulted with Action Drive being the predominant elements in the style of Pak Mat Jedok as Tok Puteri in Main Puteri performance.